Cálculo automático de pontes de eixo curvo - Corrêa, Jarbas de Souza (1980)
The purpose of this study is the automatic analysis of principal beams of the curved bridges, considering them isolatad from the columns. The computer program developed allows the analysis of bridges with any variation in curvature and cross section. At first, a brief description of bridges and the development of the thaoretical concepts involved are presented, after that, some practical examples and the computer program in FORTRAN language are given.